Pengaruh Ukuran Perusahaan, Profitabilitas, dan Leverage terhadap Manajemen Laba (Studi Empiris Pada Perusahaan Subsektor Farmasi yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2017-2022) - Rizqi, Purisma Fathnia; Harahap, Muhammad Nasim (Jurnal Ilmiah Wahana Pendidikan, 2024)
The purpose of this study is to find out how company size, profitability, and leverage affect earnings management in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange from 2017 to 2022. The research period uses secondary data for 6 years, from 2017 to 2022. The information used in this study was obtained from the websites of each related company between 2017 and 2022 as well as financial report data on the Indonesia Stock Exchange. On the Indonesia Stock Exchange there are 11 pharmaceutical companies that are the population in this study. However, only 9 pharmaceutical companies were selected as samples in the purposive sampling research technique. Descriptive verification is the research methodology used. While the data analysis technique uses the classical assumption test and multiple linear regression analysis. SPSS Software Version 25 is used to process the data. Based on the results of research conducted, it shows that Company Size, Profitability, and Leverage simultaneously or equally have a significant effect on Earnings Management. However, partially the size of the company has no effect and is not significant on earnings management. Profitability partially has a positive and significant effect on earnings management. Leverage partially has a negative and significant effect on earnings management in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 – 2022.